Strategy of profit organizations in pre-crisis and crisis situations - O. V. Sergienko; O. Y. Patlasov (Вестник СибАДИ)
The paper dwells on the main approaches for development and selection of anti-crisis management’s strategy of a profit organization with the influence of environment and priorities of its development. During the crisis every company develops anti-crisis strategy based on the crisis’ scope, priority objects of development. As practice shows, success or failure in overcoming crisis depends on the right response, from the direction of the company, to external challenges and internal threats.